Constructions of patient agency in healthcare settings: Textual and patient perspectives. (March 2015) - Hunter, Judy; Franken, Margaret; Balmer, Deborah
Abstract: In healthcare settings, patient agency is variously represented and circumscribed through the language of health information texts, the discourses of health practitioners, and patient/practitioner interaction. Patients, as well, construct their identity and act as agents in various ways as they encounter the healthcare system and strive to manage their health conditions. This paper explores the notion of patient agency in healthcare settings and healthcare texts. The data comes from a health literacy project, commissioned by a New Zealand primary healthcare provider, and a Ph.D. project exploring the mediation and use of health information texts in a hospital setting. It draws on multiple data sources: text analyses on over 100 cardiovascular and diabetes information brochures, focus group interviews with cardiovascular and diabetes patients, and observations of patients׳ interactions with text in a hospital cardiovascular unit. These sources of data show ways that patient agency is represented and restricted and that identity is often constructed in conflict with patients׳ own conceptions of agency. The focus group interviews and hospital observations show how patients contest, accept, reject, and negotiate the identities constructed of them. As well, our data shows the contrast between patients׳ enacting agency and healthcare professionals׳ prescribed agency as compliance. Our sources of data confirm that knowledge of condition and care and associated agency are contingent on a constellation of affordances. Highlights: The healthcare sector circumscribes patient agency as responsibility and compliance. Patients often struggle to become knowledgeable and manage their condition. For the healthcare sector education was knowledge transmission; the patients learned in many ways.